Global trends in oncology research: A mixed‐methods study of publications and clinical trials from 2010 to 2019. Issue 1 (11th June 2022) - Akiki, Vincent; Troussard, Xavier; Metges, Jean‐Philippe; Devos, Patrick
Abstract: Purpose: To evaluate the cancer research effort of some major countries over two 5‐year periods (2010–2014 and 2015–2019) on the basis of scientific publications and interventional clinical trial metrics and to analyze the relationship between research effort and cancer burden (incidence and mortality). Materials and Methods: Clinical trials were extracted from ClinicalTrials.gov using a specific query. Publications were identified in Web of Science (WoS) using a query based on keywords and were then analyzed using InCites, a bibliometric tool. Bibliometric indicators were computed per country and per period. Results: During 2010–2019, 1 120 821 cancer‐related publications were identified in WoS, with 447 900 and 672 921 (+50%) articles respectively published in 2010–2014 and 2015–2019. Meanwhile, 38% and 7% of the articles were published in oncology and cell biology journals, respectively. Exactly 30% of the published articles were contributed by the USA. In the study period, China strongly increased its production and overspecialization. Apart from China, which had a low normalized citation impact (NCI), almost all countries increased their NCIs; in particular, France's NCI increased from 1.69 to 2.44. As for clinical trials, over 36 856 were opened worldwide during that period. Over 17 000 (46.5%) opened in the USA, which remained the leader during the study period. China ranked second worldwide in terms of the number of open trials in 2015–2019. Results revealed that the 17 cancer localizations versus cancer burden and research effort showed no evident relationship. Conclusion: The results may provide a scientific basis for decision making for continued research. Based on bibliometric data, this type of study will aid public health policymaking and lead to a more transparent public fund allocation.